Deposition of crystalline copper films from tetranuclear copper (II) complexes without application of reducing atmosphere - Shahid, M.; Mazhar, M.; Hamid, M.; Brien, P.O'; Malik, M.A.; Helliwell, M. (John Wiley & Sons, 2010)
Crystalline copper films were deposited by aerosol-assisted chemical vapor deposition (AACVD) in the absence of hydrogen from two newly synthesized complexes [Cu(deae)(TFA)](4)center dot 1.25THF (1) and [Cu(4)(OAc)(6)(bdmap)(2)(H(2)O)(2)]center dot 4H(2)O (2) [deae = N, N-diethylaminoethanolate, TFA = trifloroacetate, OAc = acetate and bdmap = 1,3-bis(dimethylamino)-2-propanolato]. These precursors were prepared in high yield using mixed ligands and crystallized in tetragonal and triclinic crystal systems with space groups 14(1)/a and P-1. Complexes 1 and 2 thermally decomposed at 290 and 250 degrees C, respectively, to yield copper films which were characterized by SEM/EDX for their morphology and composition and PXRD for their crystallinity and phase. These films have smooth morphologies with particle sizes within the range of 0.3-0.6 mu m and may find applications in fabrication of ultralarge-scale integrated circuits. Copyright (C) 2010 John Wiley & Sons, Ltd.